Analisis sifat listrik nanokomposit Fe3O4/PVDF yang disintesis dengan metode sol gel untuk aplikasi elektroda baterai lithium ion (Analysis of the electrical properties of Fe3O4 / PVDF nanocomposites synthesized by sol gel method for lithium ion battery electrode applications ) - - Rahmi; - Ramli; Yenni Darvina (PILLAR OF PHYSICS, 2018)
As technology develops at this time, all electronic components require a voltage source. One source of voltage is the battery. West Sumatra is one area that is rich in eccentrics. Iron ore content in Tiram Beach in West Sumatra is 34.015%, followed by other elements as pollutants. However, basically there is still a lack of public knowledge about nano materials. Nano composite is a mixture of matrix and filler with a certain composition. This study aims to find out which is good for making lithium batteries. The requirement for making lithium batteries is high conductivity and high capacitance. At this time also look at the properties of fe3O4 nano compresses. Based on experiments that have been carried out will produce Fe3O4 and PVDF, the greater the value of electrical conductivity and capacitance will be. The conductivity values obtained were 437082.9 S / m, 8337755 S / m, 753969 S / m, 9300430 S / m, 1034708 S / m and the capacitance value was 35.94μF, 37.8 μF, 5.2 μF, 194 μF, 2.68 μF. Based on the results that can be used is a large amount of 10 ml: 30 ml.